Seasonal Variations in Baltic Sprat ( Sprattus sprattus balticus ) Chemical Composition and Their Impact on Smoked Sprat Quality - Santa Puke; Ruta Galoburda (Polish Journal of Food and Nutrition Sciences)
This study aimed to evaluate the chemical composition of Baltic sprats throughout the fishing season (November-March) while examining the texture and color of smoked sprats produced after that. Smoked sprats were produced from fresh fish and fish from the same batches after one year of frozen storage and thawing. The protein content in raw sprats remained stable with lysine and leucine exhibiting the highest content among essential amino acids. The lipid content showed an inverse correlation with moisture content during fishing season. Throughout the fishing season, there was a notable reduction in fatty acid content, particularly in n 3 fatty acids. The lowest values of atherogenicity and thrombogenicity indexes were recorded in the autumn sprats, while the hypocholesterolemic to hypercholesterolemic fatty acid ratio was the highest in this fish, indicating its higher nutritional value. The moisture content increased from 62.4 g/100 g in the fish from the autumn catch to 70.0 g/100 g in those from the spring; thereby, impacting the physical properties of smoked sprats such as texture, color, and pH. The observed decrease in hardness, as well as reduced redness and yellowness of smoked fish sourced from the spring catches was likely attributed to the higher moisture content. Smoked sprats produced from frozen sprats exhibited lower hardness and slightly darker color.